Aggressive Attitudes in The Novel Street Kid by Judy Westwater: Physichology of Literature - Untung; Anita Rosanty; Mariyatul Kiptiyah (FKIP, Universitas Lakidende Unaaha, 2022)
The objectives of this research are to reveal the causes of aggressive attitudes toward Judith Richardson (JR) in Street Kid by Judy Westwater. This research used qualitative approach that seen from literary psychology point of view, using collecting data method such as documentation with descriptive technique and content analysis. The research data focuses to the causes of aggressive attitudes toward JR. Related to the aims of research, analysis result show that the causes of aggressive attitude toward JR consist of two factors, there are (a) environment and (b) poverty. That is related to the trait of the characters that has intention to do aggression and that intention will be actualized with an action so JR as the target felt the aggression attitude.